Порівняльна характеристика деяких видів роду Тhymus L. в умовах Херсонської області та Південного узбережжя Криму (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The four species and one hybrid of the genus Thymus cultivated in the experimental farm «Novokakhovskoe» (Kherson area) are studied. The essential oil obtained from these species was analyzed with 30 components identified. Among them, thymol revealed to be the basic component with the considerable difference in oil composition in Kherson area and Nikitsky garden.
Keywords: Thymus vulgaris, Th. striatus, Th. serpyllum, Th. kotschyanus, Kherson region, the Nikitsky botanical garden, essential oil composition.